Navigating the Nexus: Anesthetic Management of Craniotomy for Brain Abscess in a Pediatric Patient with Uncorrected Tetralogy of Fallot - Anak Agung Ngurah Aryawangsa; Ida Bagus Krisna Jaya Sutawan (Journal of Anesthesiology and Clinical Research, 2025)
Introduction: Tetralogy of Fallot (TOF) is the most prevalent cyanotic congenital heart disease, predisposing patients to brain abscesses via right-to-left shunting that bypasses pulmonary bacterial filtration. Anesthetic management for craniotomy in pediatric patients with uncorrected TOF and a concurrent brain abscess presents a formidable challenge, requiring meticulous integration of neuroanesthetic and cardiac anesthetic principles. Literature detailing comprehensive perioperative anesthetic strategies for this specific dual pathology remains scarce. Case presentation: An 11-year-old male with uncorrected TOF and a large left frontoparietal brain abscess with significant mass effect underwent emergent craniotomy and abscess evacuation. Preoperative echocardiography confirmed TOF with severe pulmonary stenosis and right-to-left shunting. Anesthetic induction was achieved with titrated ketamine and propofol, followed by fentanyl and rocuronium. Maintenance involved sevoflurane, oxygen-air mixture, and intermittent fentanyl and rocuronium, focusing on normovolemia, normocapnia to slight hypocapnia, and invasive hemodynamic monitoring. Phenylephrine was utilized for blood pressure support. The perioperative period was uneventful, with the patient experiencing no neurological or cardiac complications. Conclusion: This case underscores the critical importance of a tailored anesthetic approach, integrating neuroprotective strategies with meticulous cardiovascular management, in children with uncorrected TOF undergoing major neurosurgery. Comprehensive preoperative assessment, vigilant intraoperative monitoring, strategic pharmacological interventions, and a deep understanding of the complex pathophysiology are paramount to preventing cyanotic spells, managing intracranial pressure, and ensuring a successful outcome in this high-risk cohort.